Mam-Kind, a novel peer support intervention of motivational interviewing for breastfeeding maintenance: a feasibility study in the UK. (November 2016) - Copeland, Lauren; Merrett, Laura; Grant, Aimee; Phillips, Rhiannon; Tedstone, Sally; Sanders, Julia; Robling, Mike; Rollnick, Stephen; Gobat, Nina; Hunter, Billie; Paranjothy, Shantini
Abstract: Background: The benefits of breastfeeding for the health of babies and mothers are well known, but in the UK less than half of the 81% of women who start breastfeeding continue beyond 6 weeks. WHO recommends 6 months' exclusive breastfeeding. Breastfeeding peer-support was found to be effective for breastfeeding maintenance in low or middle income countries, but not in UK-based studies. We developed a breastfeeding peer-support intervention using motivational interviewing and tested the feasibility and acceptability of delivering it to pregnant women and new mothers. Here we consider findings from qualitative interviews and report on the acceptability of this intervention. Methods: This feasibility study was conducted across three sites in Wales and England. After delivery of the 6 month intervention to 70 participants we conducted semi-structured interviews with a purposive sample of mothers who provided informed consent (n=28), health-care professionals (14), and peer supporters (8). Thematic analysis was used to assess the acceptability of the intervention. Findings: Mother-led contact was maintained with peer supporters via phone, text, face-to-face, and social media. Mothers reported that the peer-supporters provided infant feeding information and reassurance. Mothers described them as being non-judgmental and more contactable than were health professionals. Peer supporters reported that they were not consistently notified of a birth. Health-care professionals suggested that integration with existing services was feasible. Despite training for motivational interviewing, peer-supporters reported difficulties in providing it within the context of the study, for example changing from an expert role to a collaborative approach. Interpretation: We developed an intervention that is acceptable to mothers, health professionals, and peer-supporters. The issues surrounding notification of birth highlight the importance of study awareness and communication with health professionals. The difficulties with motivational interviewing need further exploration and adaptation of training. The next step will be to assess the effectiveness of this intervention for maintenance of breastfeeding. Funding: National Institute for Health Research Health Technology Assessment programme.